AUTISTHERAPIBOT: Autonomous robotic autism therapists assistant for autistic children - Rahim, M.H.B.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
Recent studies unravels that Autistic Spectrum Disorder which include Asperger Syndrome have many bad impacts. Among the symptoms of ASD are difficulties to focus that leads to difficulties in learning especially to those ASD children. Thus, the objective of this project is to investigate the current teaching method used by the autism therapists and solve the weaknesses via robotic means. The NXT will be used in order to aid the therapists in educating those children with ASD. Upon the completion of the prototype, it will be tested against the autistic children to check on the efficacy of the developed prototype. The project will focus on how to attract the autistic children into learning via the usage of robotic application. In a preliminary investigation, multiple robotic designs and programming approach are studied to produce a robotic application that can assist therapists and engage with the target autistic children in order to facilitate their process of learning. Interviews with the therapists and live observation at the selected special school are conducted to understand the traditional learning process that are used by the therapists and identify the weaknesses in it to improvise it. The significance of this robotic application is to fulfill the depravedness in the learning capabilities of the autistic children and also to assist the therapists in their daily routine. Â© 2014 IEEE.